Rasch Model Analysis of Spatial Visualization Test Items on the Pythagorean Theorem for Junior High School Students Using Ministep - Syfa Istiqomah; Desy Lusiyana; Rifqi Hidayat (MASI Mandiri Edukasi, 2025)
The lack of valid and reliable test instruments to measure junior high students’ spatial visualization skills, especially regarding the Pythagorean Theorem, prompted this study. The goal of this research is to assess the quality of spatial visualization test items related to the Pythagorean Theorem for junior high students. This study used a quantitative descriptive approach with Rasch Model analysis via Ministep software. The developed instrument included 11 essay questions administered to 30 ninth-graders through purposive sampling. Results showed that 5 items were valid, while 6 needed revision. The instrument’s reliability coefficient was 0.91 (high). Based on difficulty, there were 3 easy, 2 moderate, and 6 difficult items. This instrument meets Rasch Model standards and is suitable for measuring junior high students’ spatial visualization abilities concerning the Pythagorean Theorem, serving as a reference for designing more accurate and representative math assessments..